2021
DOI: 10.1371/journal.pone.0248584
|View full text |Cite|
|
Sign up to set email alerts
|

Improvement of loperamide-induced slow transit constipation by Bifidobacterium bifidum G9-1 is mediated by the correction of butyrate production and neurotransmitter profile due to improvement in dysbiosis

Abstract: A treatment option for constipation that improves the quality of life is needed since available laxatives do not effectively improve the quality of life in patients with constipation. A significant association between gut dysbiosis and constipation is recognized, suggesting that probiotics may be an important option for management of constipation. The underlying mechanism by which probiotics improve constipation remains unclear. In this study, we aimed to evaluate the effects of the probiotic Bifidobacterium b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Various strains of B. bifidum have been demonstrated to improve several physical conditions, including rhinoconjunctivitis-specific quality of life [22], reducing milk allergies in infants [23], and improving the serum cholesterol metabolism of subjects with dyslipidemia [24], irritable bowel syndrome [25], and Parkinson's disease (PD) [27]. B. bifidum G9-1 (BBG9-1) potentially improves dysbiosis, which results in modulations of organic acids and neurotransmission (including dopamine) [26]. Furthermore, neurochemical mechanisms that interfere with monoamine neurotransmitter synthesis have been implicated in ADHD pathophysiologies [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various strains of B. bifidum have been demonstrated to improve several physical conditions, including rhinoconjunctivitis-specific quality of life [22], reducing milk allergies in infants [23], and improving the serum cholesterol metabolism of subjects with dyslipidemia [24], irritable bowel syndrome [25], and Parkinson's disease (PD) [27]. B. bifidum G9-1 (BBG9-1) potentially improves dysbiosis, which results in modulations of organic acids and neurotransmission (including dopamine) [26]. Furthermore, neurochemical mechanisms that interfere with monoamine neurotransmitter synthesis have been implicated in ADHD pathophysiologies [46].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, heat-inactivated B. bifidum MIMBb75 (SYN-HI-001) has been shown to substantially alleviate the symptoms of irritable bowel syndrome [25]. B. bifidum G9-1 (BBG9-1) improves dysbiosis, which results in an increase in organic acids and improved neurotransmission (including dopamine) [26]. In addition, a mixture of probiotics containing Lactobacillus species and B. bifidum could improve rotational behavior, cognitive function, and neuronal damage in patients with Parkinson's disease (PD) [27].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies suggested that specific probiotics helped reduce bowel transit time. Recent research found that Bifidobacterium bifidum G9-1 ( 23 ) and Lactobacillus rhamnosus strains relieved loperamide-induced constipation ( 24 ). At the same time, the effect of Bifidobacterium animalis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some low-fat calorie sweeteners have also been associated with increased concentrations in Bifidobacterium genus. Bifidobacterium is correlated with a myriad of beneficial effects in the human host through alterations to neurotransmitter profiles, including dopamine [ 34 ], and is a common bacterial genus used in many probiotics. Additionally, foods such as kiwifruit have been shown to increase Bifidobacterium species within in-vitro fecal fermentation models, which also enhance the production of key dopamine precursor l -dihydroxyphenylalanine (L-DOPA).…”
Section: Changes In Nutrients Dopamine and Microbiotamentioning
confidence: 99%